PENERAPAN KURIKULUM 2013 DALAM PENGEMBANGAN KARAKTER SISWA DI MA AL-FALAH BRANTA TINGGI TLANAKAN PAMEKASAN - Fatihah Fatihah; Moh. Hafid Effendy (re-JIEM (Research Journal of Islamic Education Management), 2019)
Curriculum becomes one of the most important components in education. It is able to determine how the process of education will be conducted. In this case, curriculum will contribute big impact toward the students’ knowledge, attitude and character. In this research, there are four focuses to be investigated, they are: first, what are the steps of the school principal in implementing the curriculum 2013 as to develop the students’ character at MA Al-Falah Branta Tinggi Tlanakan Pamekasan? Second, what are the teacher’s steps in the learning process to develop the students’ character at MA Al-Falah Branta Tinggi Tlanakan Pamekasan? Third, what are the supporting factors in implementing the curriculum 2013 as to develop the students’ character at MA Al-Falah Branta Tinggi Tlanakan Pamekasan? Fourth, what are the inhibiting factors in implementing the curriculum 2013 as to develop the students’ character at MA Al-Falah Branta Tinggi Tlanakan Pamekasan?